Project-based Learning for Environmental Sustainability Action - Sharon Bramwell-Lalor; Keith Kelly; Therese Ferguson; Carol Hordatt Gentles; Carmel Roofe (Environmental Association of Southern Africa, 2020)
The quest for social and economic development coupled with a growing population has led to complex and unsustainable interactions between humans and the natural resources of planet Earth. One approach to addressing complex, 'wicked' problems involves closing the gap between the sustainability knowledge of individuals and the competencies for positive environmental behaviours. Projectbased learning is one teaching-learning strategy which provides opportunities for cultivating a wide range of sustainability competencies to close this gap. Two cases are presented in this paper in which project-based learning was used for fostering environmental competencies and advancing sustainability. One relates to teachers in a graduate course, and the other, to students using an online learning platform. Evaluation of various qualitative documents and artefacts produced by participants revealed that i) teachers and students were motivated and enabled to take action on environmental and sustainability issues through project-based learning ii) participants' environmental knowledge and sustainability competencies such as communication and collaboration skills were enhanced. School administrators should therefore encourage a culture where project-based learning is infused into the curriculum, and teachers' collaborative efforts regarding projects are supported.